The Evolution of Marketing Strategy: Integrating Marketing Theory and Behavioural Theory through Literature Review - Firasghani, Muhammad Almy; Suryati, May; Arfiq, Muhammad; Sandriyan, Muhammad; Gustina, Ni Luh Zallila (Asosiasi Ahli Administrasi Indonesia, 2025)
The marketing landscape has experienced considerable changes over the years, largely due to the merging of marketing theory with behavioural theory. This journal article seeks to investigate the progression of marketing strategies by addressing crucial questions such as: How have marketing theories evolved in response to shifting consumer behaviours? What influence does behavioural theory have on the development of effective marketing strategies? The primary approach taken in this literature review is a systematic examination of existing research, incorporating a wide range of studies that highlight the convergence of marketing and behavioural theories. The results indicate that incorporating behavioural insights into marketing strategies significantly boosts their effectiveness, especially in the realm of social marketing. The challenges and opportunities present in social marketing, illustrating that behavioural methods can result in notable improvements in public health outcomes. That interventions using social marketing techniques lead to quantifiable behavioural changes within the general population. In summary, the amalgamation of marketing and behavioural theories enhances the comprehension of consumer dynamics while providing marketers with innovative strategies to effectively engage and influence their target audiences. This article contributes to the ongoing dialogue regarding the evolution of marketing, offering valuable insights for both academics and practitioners aiming to navigate the intricacies of contemporary marketing environments.